Housing for All in India and Its Future in Sustainable Development - Nadia Shah (Journal of Global Initiatives, 2018)
The Government of India has been challenged with a growing housing demand for more than half a century, since its independence in 1947. The shift in the country’s population from rural to urban creates an emerging dynamic in the housing gap. While India continues to move forward, already the world’s fastest growing economy, in the realm of manufacturing and services, the housing demand continues to increase. This paper investigates the causes and consequences of the housing shortage in India, by examining the country’s past policies that have been public housing, sites and services, slum upgrading and self-help programs, and their limitations. It addresses the future discourse of housing policies in the framework of the global ‘sustainability’ concept and concludes that a self-help model based on people, planet and prosperity can create cost efficient and environment friendly housing through participatory actions, for the sustainable growth of India’s urban areas. The article highlights the need to understand the complexities within the framework of self-help and self-build projects in informal settlements of India by exploring both the process and products.